Mimetic Learning at Work - Billett, Stephen. author. aut Link
XV, 107 p.
Keywords: This book examines the concept of mimetic learning at work and discusses processes of observation, imitation and practice that is central to learn through and for work. It elaborates the contributions to that learning from the experiences and lessons gained from social sources and the natural world, and individuals’ particular ways of engaging in and responding to what is experienced in the circumstances of occupational practice. The book presents an account of how securing occupational capacities needs to be seen primarily as a learning process and provides an explanatory account of that process. It proposes that this process is the most common and enduring means of human learning of occupational practices and associated development. The book is well aligned with and informs current discussions on and considerations of how individuals learn through and for work. Up until now, such considerations are usually based on educational precepts and practices (i.e. associated with programs and teaching) and look to the circumstances of work practice and deliberate ways of augmenting or promoting what has been learnt in educational programs. However, analyses of the development of occupational capacities emphasize the importance of individuals’ learning processes, albeit those exercised within and outside of direct guidance by more expert partners. The latter is important as much of the learning and development across individuals’ working lives occurs outside of circumstances of direct guidance or instruction.